Development Model Of Halal Destination: A Literature Review - Lila Bismala; Gustina Siregar (Proceeding International Seminar of Islamic Studies, 2019)
Tourism plays an important role in the economy because it can absorb a lot of labor, empower the community, the emergence of a creative economy. The increasing number of Muslim population, making halal tourism a strategic issue to be observed. Guaranteed halal destinations is very important to attract tourists, so they feel safe with their choices.This article intends to model the development of halal destinations, by including elements of consumer behavior and attributes in the selection of halal destinations. Consumer behavior is very important in influencing the decision / selection of products or services to be consumed. While the halal attribute is an indicator of consumers in choosing a halal destination. This research is a literature study because it develops the model through a literature review. The halal destination development model must consider consumer behavior which includes cultural factors, personal factors, psychological factors, social factors, values, motivation, self-concept and personality, expectations, attitudes, perceptions, satisfaction and trust and loyalty. The attributes of halal destinations that are expected to be fulfilled by the destination management include: having Islamic values and which also includes halal food products, non-alcoholic drinks, halal hotels, clean, safe, the availability of comfortable prayer rooms, and other facilities.